2021
DOI: 10.1111/lasr.12570
|View full text |Cite
|
Sign up to set email alerts
|

Police fairness and legitimacy across the post-communist divide in Europe

Abstract: In the present study, we compared two European regions with deeply contrasting policing traditions-post-communist countries and established democracies-to explore whether political history may have long-term consequences for police-public interactions. Using data from 26 countries that participated in the 2010 European Social Survey, we first measured and compared the prevalence of police-initiated contact and satisfaction with contact once it took place. We found that both tended to be higher in established d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…Moreover, this effect was similar in magnitude to that of the original specification ( g = −0.38, 95% CI [−0.59, −0.17]). Finally, one study measuring attitudes toward the police (Baćak & Apel, 2021), two studies measuring mental health issues (Baćak & Nowotny, 2020; Dennison & Finkeldey, 2021), and one study measuring self‐reported crime/delinquency (Lee et al, 2017) used measures of police stops that were limited to unfair, false, or unsatisfactory stop experiences. Given that these experiences may have separate impacts on effect sizes, we re‐estimated each model while excluding these studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, this effect was similar in magnitude to that of the original specification ( g = −0.38, 95% CI [−0.59, −0.17]). Finally, one study measuring attitudes toward the police (Baćak & Apel, 2021), two studies measuring mental health issues (Baćak & Nowotny, 2020; Dennison & Finkeldey, 2021), and one study measuring self‐reported crime/delinquency (Lee et al, 2017) used measures of police stops that were limited to unfair, false, or unsatisfactory stop experiences. Given that these experiences may have separate impacts on effect sizes, we re‐estimated each model while excluding these studies.…”
Section: Resultsmentioning
confidence: 99%
“…Attitudes toward the police and self‐reported crime/delinquency were also measured using self‐report surveys and interviews. Common outcomes for attitudes toward the police included scaled or ordinal measures of police legitimacy (Baćak & Apel, 2021; Murray et al, 2021; Tyler et al, 2014), respect (Friedman et al, 2004; Harris & Jones, 2020; Singer, 2013), trust (Friedman et al, 2004; Murray et al, 2021; Singer, 2013), satisfaction (Wheelock et al, 2019), and overall negative attitudes (Rosenbaum et al, 2005; Swaner & Brisman, 2014). For the six studies measuring self‐reported crime/delinquency, these measures were operationalized as composite counts or scales that included multiple forms of adolescent or adult criminality (Slocum et al, 2016; Wiley & Esbensen, 2016; Wiley et al, 2013), drug use (Dennison & Finkeldey, 2021), or general non‐compliance with the law (Murray et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations